1993
DOI: 10.1111/j.1365-2958.1993.tb01660.x
|View full text |Cite
|
Sign up to set email alerts
|

Lactococcus lactis: high‐level expression of tetanus toxin fragment C and protection against lethal challenge

Abstract: To determine if the food-grade bacterium Lactococcus lactis holds promise as a vaccine antigen delivery vector we have investigated whether this bacterium can be made to produce high levels of a heterologous protein antigen. A regulated expression system has been developed which may be generally suitable for the expression of foreign antigens (and other proteins) in L. lactis. The system utilizes the fast-acting T7 RNA polymerase to transcribe target genes, and provides the first example of the successful use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
131
1
2

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(140 citation statements)
references
References 27 publications
(7 reference statements)
5
131
1
2
Order By: Relevance
“…This plasmid, designated pIL1331, was replicative only in E. coli. Then, the EcoRI-HindIII fragment from pIL1331 was transferred to pMIG1 (39); the resulting plasmid, designated pIL1357, was replicative in L. lactis. Plasmids pWWT7 and pMIG1 were kindly provided by J. Wells.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This plasmid, designated pIL1331, was replicative only in E. coli. Then, the EcoRI-HindIII fragment from pIL1331 was transferred to pMIG1 (39); the resulting plasmid, designated pIL1357, was replicative in L. lactis. Plasmids pWWT7 and pMIG1 were kindly provided by J. Wells.…”
Section: Methodsmentioning
confidence: 99%
“…A derivative, replicative in L. lactis, was constructed by cloning the EcoRI-HindIII fragment harboring the T7 RNA polymerase promoter in front of abiD1 from pIL1327 ( Fig. 1) into pMIG1 (39). The recombinant plasmid obtained was designated pIL1332.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…LAB is potential probiotics that provide benefits to human health [116]. Modified LAB could also be used as live vaccines or vaccine delivery systems [117]. It has been shown that the genetically modified L. lactis can survive and colonize the digestive tract of humans [118] and gnotobiotic mice [119].…”
Section: Discussionmentioning
confidence: 99%
“…It is generally recognized as safe by the U.S. Food and Drug Administration. Many heterologous proteins have been expressed in L. lactis (11,12,18,23,31,42,53), and immunization with these strains elicits immune responses specific to heterologous antigens (43,52,55). However, we are aware of only one report (55) that shows that mucosal immunization with a lactococcal vaccine can reduce infection.…”
mentioning
confidence: 91%